In a certain candy store, 3 pounds of candy and 2 pounds of mints cost $10.80, and 1 pound of candy and 3 pounds of mints cost $5.35. What i

Question

In a certain candy store, 3 pounds of candy and 2 pounds of mints cost $10.80, and 1 pound of candy and 3 pounds of mints cost $5.35. What is the cost per pound of the candy and the mints?

If m = price of mints and c = price of candy, then which of the following expressions is equal to 5.35?

in progress 0
Trúc Chi 1 year 2021-09-03T17:19:42+00:00 1 Answers 4 views 0

Answers ( )

    0
    2021-09-03T17:20:58+00:00

    Answer:

    m = 0.75well 1.7 bc 5.35/3=1.7 This is the cost per pound of the mints.

    Step-by-step explanation:

    From this sentence >> 3 pounds of candy and 2 pounds of mints cost $10.80

    you can make-up an equation >> 3c + 2m = 10.80 right?

    That’s your first equation, 3c + 2m = 10.80 … (1)

    and from this sentence >> 1 pound of candy and 3 pounds of mints cost $5.35

    you can make-up an equation >> c + 3m = 5.35 … (2)

    you can use various methods here, like graphing, substitution, comparison, and elimination method.

    Let’s try using substitution method.

    3c + 2m = 10.80 … (1)

    c + 3m = 5.35 … (2) << here you can come up with c = 5.35 – 3m then substitute it to (1)

    3c + 2m = 10.80 … (1)

    3(5.35 – 3m) + 2m = 10.80

    16.05 – 9m + 2m = 10.80

    -7m = -5.25

    m = 0.75 <<This is the price of the mint

    to get the price of candy, simply substitute m = 0.75 to (1) or (2) if you want, it depends on you.

    Either way, you will have the same answer.

    Let’s try substituting in (1)

    3c + 2m = 10.80 … (1)

    3c + 2(0.75) = 10.80

    3c + 1.5 = 10.80

    3c = 9.3

    c = 3.1 <<this is the price of the candy

    was difiqult hope this helps!!!!!

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )